Hydrothermal Synthesis of Zeolite T from Kaolin using Two Different Structure Directing Agents - Sazmal E., Arshad; Lutfor, M. R.; Sarkar, Shaheen M.; Eddy F., Yusslee; Siti Z., Patuwan (Institute of Physics Publishing, 2017)
Zeolite T were synthesized from molar chemical composition of 1 SiO2: 0.04 Al2O3: 0.26 Na2O: 0.09 K2O: 14 H2O in form of homogenous milky solution in presence of two different structure directing agents of TMAOH and TEAOH respectively. Modification for composition of silica were using metakaolin from calcined kaolin at 750 ˚C in 4 h while molar composition of each different SDA were variated from 0.05, 0.10, 0.15, 0.20 and 0.25. The homogenous mixture was left at room temperature for 24 h before undergoing hydrothermal synthesis at 100 ˚C for 168 hours. Synthesized samples filtered and aged at 120 ˚C for 2 h and each samples were calcined at high temperatures(545oC for TMAOH and 520oC for TEAOH) for templates removal before characterization using XRD and SEM. Crystallization of zeolite T in major form were only at molar ratio of 0.10 of TMAOH while in TEAOH showed species evolution of zeolite T into zeolite L and W for the other molar ratios.